The Application of an Implementation Science Framework to Comprehensive School Physical Activity Programs: Be a Champion! - Moore, Justin B.; Carson, Russell L.; Webster, Collin A.; Singletary, Camelia R.; Castelli, Darla M.; Pate, Russell R.; Beets, Michael W.; Beighle, Aaron (Frontiers in Public Health, 2018)
Comprehensive school physical activity programs (CSPAPs) have been endorsed as a promising strategy to increase youth physical activity (PA) in school settings. A CSPAP is a five-component approach, which includes opportunities before, during, and after school for PA. Extensive resources are available to public health practitioners and school officials regarding what should be implemented, but little guidance and few resources are available regarding how to effectively implement a CSPAP. Implementation science provides a number of conceptual frameworks that can guide implementation of a CSPAP, but few published studies have employed an implementation science framework to a CSPAP. Therefore, we developed Be a Champion! (BAC), which represents a synthesis of implementation science strategies, modified for application to CSPAPs implementation in schools while allowing for local tailoring of the approach. This article describes BAC while providing examples from the implementation of a CSPAP in three rural elementary schools.